Hollow fiber-protected liquid-phase microextraction followed by high performance liquid chromatography for simultaneously screening multiple trace level β-blockers in environmental water samples. Issue 15 (7th August 2015) - Li, Qinglian; Jing, Shaojun; Zhang, Jinfeng; Zhang, Lin; Ran, Congcong; Du, Chaohui; Jiang, Ye
<x xml:space="preserve">Abstract</x> A two-phase hollow fiber liquid-phase microextraction (HF-LPME) pretreatment technique was developed for simultaneously screening multiple β-blockers.